Front Cover: Synthesis and Reactivity of Iron– and Cobalt–Dinitrogen Complexes Bearing PSiP‐Type Pincer Ligands toward Nitrogen Fixation (Eur. J. Inorg. Chem. 32/2017). Issue 32 (21st July 2017) - Imayoshi, Ryuji; Nakajima, Kazunari; Takaya, Jun; Iwasawa, Nobuharu; Nishibayashi, Yoshiaki
Abstract : The cover picture shows the newly designed iron– and cobalt–dinitrogen complexes bearing PSiP‐type pincer ligands, which work as effective catalysts for the transformation of molecular dinitrogen into silylamine as ammonia equivalent under ambient reaction conditions. We believe that these results contribute to the further development of the catalytic transformation of molecular dinitrogen with transition metal dinitrogen complexes as catalysts under mild reaction conditions. Details are discussed in the article by Y. Nishibayashi et al. on page 3769 ff (https://doi.org/10.1002/ejic.201700569 ). For more on the story behind the cover research, see the Cover Profile (https://doi.org/10.1002/ejic.201700863 ).